Finite Element (FE) Modeling of Indirect Tension to Cylindrical (IT-CY) Specimen Test for Damping Asphalt Mixtures (DAMs) - Jiandong Huang; Tianhong Duan; Yuantian Sun; Lin Wang; Yawei Lei (Advances in Civil Engineering)
DAMs have recently been developed to be used as the damping layer in the so-called antivibration pavement to mitigate the effects of traffic-induced vibration while rare finite element (FE) modeling has been conducted to simulate the indirect tension to cylindrical (IT-CY) specimen test for DAMs. In the present study, the methods for the viscoelastic characterization of DAMs and the techniques to characterize the viscoelastic behavior of DAMs in FE modeling were proposed. The FE model to simulate the IT-CY test was constructed, and it was verified through the corresponding laboratory test. Good agreements were noted between the simulation results and testing results demonstrating that the FE model can provide the accurate prediction of the mechanical behavior of DAMs.